Tibial Onlay Posterior Cruciate Ligament Reconstruction: Surgical Technique and Results - Salim, Rodrigo; Nascimento, Felipe Marques do; Ferreira, Aline Miranda; Oliveira, Luciano Fonseca Lemos de; Fogagnolo, Fabricio; Kfuri, Mauricio (The Journal of Knee Surgery, 2018)
The posterior cruciate ligament (PCL) is a fundamental structure in knee kinematics. PCL tears may lead to adverse consequences, such as impaired functional performance and an increased risk of osteoarthritis. Although surgical treatment is a well-established option for the patients of PCL rupture, many surgeons opt for conservative treatment because of the lack of consensus in the orthopedic literature concerning the best surgical method with less risk of iatrogenic lesions to the neurovascular structures in the popliteal region. Here, we describe an onlay technique for PCL reconstruction, which has some advantages over the traditional transtibial and over inlay techniques. The technique described in this study avoids the “killer angle”—frequently considered the cause of laxity of the reconstructed ligament—while simultaneously permitting safe retraction of the neurovascular structures without the need for a change in the patient's position. This technique has been used at our institution for approximately 10 years with very satisfactory results. The aim of this study is to describe the technique and perform a retrospective evaluation of the results of a case series.
Keywords: posterior cruciate ligament; ligament reconstruction; onlay